MENAKAR PROGRESIFITAS LEMBAGA PERADILAN DALAM MEWUJUDKAN DEMOKRASI BERINTEGRITAS - Rizqi, Alda Rifada (Fakultas Hukum Universitas Bangka Belitung, 2018)
Democracy with integrity will be realized if carried out in accordance with the will of the people as holders of sovereignty, the KPU (Komisi Pemilihan Umum) as the election organizer has the authority to make regulations that support a better democracy. KPU (Komisi Pemilihan Umum) Regulation No. 20 of 2018 as evidence that the KPU is committed to participating in preventing corrupt behavior. It was considered to have been considered as an effort to protect the interests of the people, but the regulation was submitted to a judicial review at the Supreme Court. Then, based on legal-formal considerations and based on the legal positivism of the Supreme Court, the request for the test is granted. The decision distanced itself from progressive legal values that justified the denial of what was regulated in legislation in order to put forward the values of public justice, because basically the law was made to fulfill human interests, accommodating the will of the people for the sake of order.